ANALISIS DAYA SAING DAN STRATEGI PENGEMBANGAN AGRIBISNIS GANDUM LOKAL DI INDONESIA - Lukman Muhammad Baga; Agnes A. D. Puspita (Jurnal Agribisnis Indonesia, 2013)
Wheat is an alternative food product that contains high carbohydrate, which is currently consumed by many Indonesian people in order to substitute their staple food of rice.  However, Indonesia must import large amount of this product, and during the last decade the imported volume has dramatically increased.  In 2008 the imported wheat reached 4.9 million tons. Since 2001, Indonesian Government has developed domestic wheat agribusiness which aimed to establish industrial villages of domestic wheat production.  However, due to some obstacles, the program is not successful yet. Therefore, it is needed to study the competitive position of wheat agribusiness in Indonesia.  The study’s objectives are (1) to portrait the current domestic wheat agribusiness in Indonesia, (2) to analyze the domestic wheat competitive position, and (3) to formulate strategy for developing domestic wheat agribusiness in Indonesia as an effort to fulfill some part of domestic wheat demand and to build industrial villages of wheat production. The study was conducted in 2009. Data have been analyzed by using the frame of Porter’s Diamond Theory in order to find out the competitive position of Indonesian domestic wheat agribusiness.  Afterwards, SWOT analysis is used to investigate internal strengths and weaknesses as well as external opportunities and threats of Indonesian wheat agribusiness in order to formulate the developing strategies. Finally, the approach of strategic architecture is used to arrange the formulated strategies where it can be easier to get the picture. The conclusion of Porter’s Diamond analysis showed that each subsystems of domestic wheat agribusiness in Indonesia still do not support one to another, therefore, its competitiveness becomes weak. In order to strengthen its competitiveness, domestic wheat agribusiness needs to be developed more properly by paying attention to development strategies which have been consciously formulated and put in mapping of strategic architecture.